(untitled) (Communications in Computational Physics, 2018)
We studied the dynamical phase transition in kinetic Ising ferromagnets driven by oscillating magnetic field in meanfield approximation. The meanfield differential equation was solved by sixth order Runge-Kutta-Felberg method. We calculated the transition temperature as a function of amplitude and frequency of oscillating field. This was plotted against field amplitude taking frequency as a parameter. As frequency increases the phase boundary is observed to become inflated. The phase boundary shows an inflection point which separates the nature of the transition. On the dynamic phase boundary a tricritical point (TCP) was found, which separates the nature (continuous/discontinuous) of the dynamic transition across the phase boundary. The inflection point is identified as the TCP and hence a simpler method of determining the position of TCP was found. TCP was observed to shift towards high field for higher frequency. As frequency decreases the dynamic phase boundary is observe to shrink. In the zero frequency limit this boundary shows a tendency to merge to the temperature variation of the coercive field.